A case of ecological specialization in ladybirds: Iberorhyzobius rondensis (Coleoptera: Coccinellidae), potential biocontrol agent of Matsucoccus feytaudi (Hemiptera: Matsucoccidae). Issue 3 (June 2014) - Tavares, C.; Jactel, H.; van Halder, I.; Mendel, Z.; Branco, M.
Abstract Specialization is an important attribute of a biological control agent. The maritime pine bast scale, Matsucoccus feytaudi Ducasse (Hemiptera Matsucoccidae), is an invasive species in Southeast France and the North of Italy. Iberorhyzobius rondensis Eizaguirre (Coleoptera: Coccinellidae), is a recently described ladybird species. Both adults and larvae are predaceous, feeding on egg masses of M. feytaudi, and are strongly attracted to M. feytaudi's sex pheromone. To evaluate the potential of I. rondensis as a biocontrol agent of the scale, we studied its niche breadth and prey range with emphasis on pine forests and hemipterans as tested prey. In this study, I. rondensis was found to achieve complete development only when fed on M. feytaudi egg masses (92.9% survival) and an artificial prey: eggs of Ephestia kuehniella Zeller (27.6% survival). From the 2nd instar onwards, complete development could be achieved using other prey species, although larvae had significantly higher mortality and slower development. In choice tests, M. feytaudi was the preferred prey. Surveys of the ladybird populations in the Iberian Peninsula revealed that it was found exclusively on Pinus pinaster Aiton, the sole host of M. feytaudi. The unusual specialization of I. rondensis, among other predaceous ladybirds, makes it an appropriate candidate for classical biological control of M. feytaudi.